2022
DOI: 10.1002/best.202100101
|View full text |Cite
|
Sign up to set email alerts
|

Einfluss der Stahlfaserbewehrungsarten auf den Betonversagenswiderstand von Befestigungen

Abstract: Stahlfaserbeton (SFB oder SFRC) ist aufgrund seiner vielen Vorteile ein Standardbaustoff für verschiedene Anwendungsbereiche und seine Verwendung scheint weiter zuzunehmen. Dies spiegelt sich neben zahlreichen wissenschaftlichen Veröffentlichungen und Fachkonferenzen auch in den aktuellsten Regelwerken wider, wie z. B. der DAfStb-Richtlinie Stahlfaserbeton und ihrer jüngsten Ergänzung [1], und vor allem in seiner Aufnahme in die nächste Ausgabe des Eurocode 2 [2]. Die Einbringung von Faserbewehrung zielt darau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Table 2 summarizes the ultimate loads from all tests, along with the test angles and material test results. To keep tests performed in concrete with slightly varying compressive strengths comparable, every test result is normalized to a hypothetical cube strength of exactly 25 MPa, by multiplication with the normalizing factor α = (25/f c ) 0.5 , where f c is the recorded cube compressive strength (see also Spyridis et al 19,20 for a more detailed explanation). As seen, the variations in concrete strength are relatively small compared to the results for different test angles, which implies that the fiber orientation can significantly influence the load capacity of anchors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 summarizes the ultimate loads from all tests, along with the test angles and material test results. To keep tests performed in concrete with slightly varying compressive strengths comparable, every test result is normalized to a hypothetical cube strength of exactly 25 MPa, by multiplication with the normalizing factor α = (25/f c ) 0.5 , where f c is the recorded cube compressive strength (see also Spyridis et al 19,20 for a more detailed explanation). As seen, the variations in concrete strength are relatively small compared to the results for different test angles, which implies that the fiber orientation can significantly influence the load capacity of anchors.…”
Section: Resultsmentioning
confidence: 99%
“…Vita and Sharma 15,16 established dependencies of the fiber dosage (at 40–80 kg/m 3 ) and concrete strength to the concrete break‐out capacity of bonded anchors, and in the study by Tóth et al, 17,18 previous and own investigations are treated systematically concerning the fiber content, leading to a linear dependence thereof as a predictor of the concrete break‐out strength. Spyridis et al 19,20 have carried out comprehensive experimental investigations to identify the sensitivity of the load‐bearing capacity of headed studs against concrete break‐out for a series of SFRC parameters, including various types of steel fibers, fiber dosages, as well as concrete tensile and compressive strength in pre‐cracked and uncracked concrete. They further demonstrate that improvements in all individual control parameters can lead to a significant increase in load capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Later studies by the authors [1], [10] have shown a systematic correlation between the fibre dosage but also the fibre type for both uncracked and cracked SFRC, whereby a directly proportional increase of the anchor strength can be identified with tensile properties of the concrete (e.g.…”
mentioning
confidence: 96%